Fiscal Transparency Initiative : Integration of Natural Resource Management Issues. (Policy Papers; Policy Paper, 2019)
This paper integrates into the Fiscal Transparency Code (FTC) a new fourth pillar (Pillar IV) on natural resource revenue management. This completes the pending update to the IMF's FTC, as set out by staff in 2014 (see IMF 2014a).